The Parasitic Hematophagous Worm Haemonchus contortus Inhibits Human Platelet Aggregation and Adhesion: Partial Purification of a Platelet Inhibitor - Crab, Annick; Noppe, Wim; Pelicaen, Conny; Van Hoorelbeke, Karen; Deckmyn, Hans (Thrombosis and Haemostasis, 2002)
Blood sucking parasites elaborate mechanisms to counteract the hemostatic system of their victim. Haemonchus contortus worms use several mechanisms directed against the normal platelet hemostatic function. Platelet adhesion onto collagen and fibrinogen, and the ristocetin-mediated interaction of von Willebrand Factor with glycoprotein (GP) Ib were inhibited by the protein extract of adult worms. Also platelet aggregation induced by collagen, thrombin, ADP, ristocetin or A23187 was inhibited. Although we obtained evidence for interference with fibrinogen binding to GPIIb/IIIa, the strongest inhibition was seen when the agonists collagen or thrombin were used. A small multisubunit inhibitor of collagen-induced platelet aggregation was partially purified using anion exchange chromatography, gelfiltration and RP-HPLC. The inhibitor has a pI between 4 and 6.5, elutes with a molecular weight of 23,800 Da after gelfiltration, and is part of the elaborate broad-spectrum antiplatelet activity that results in the potent synergistic anti-hemostatic cocktail produced by H. contortus.
Keywords: Haemonchus contortus, parasite; platelet aggregation; platelet adhesion; inhibitor